Investigation and analysis of the performance of external wall tiling in Singapore - Ong, Freddie Teck Khim. (2009)
Problems related to the use of external wall tiling as a building envelope has become predominant in Singapore. These problems include falling tiles, cracking, delamination and staining of tilework. In order for the building industry to have better quality buildings, there is a need to evaluate the performances of these external wall tiling systems and to recommend suitable external wall tiling details for the building industry in Singapore.